Work Function Algorithm with a Moving Window for Solving the On-Line k-Server Problem - Baumgartner, A.; Manger, R.; Hocenski, Z. (Proceedings of the ITI 2007 : 29th International Conference on Information Technology Interfaces : ITI 2007 : June 25-28, 2007, Cavtat/Dubrovnik, Croatia, 2007)
We consider a modification of the well known work function algorithm (WFA) for solving the on-line k -server problem. Our modified WFA is based on a moving window, i.e. on the approximate work function that takes into account only a fixed number of most recent on-line requests. The main motivation for using a moving window is to gain control over the prohibitive computational complexity imposed by the original algorithm. Experimental results are presented, where the performance of the modified WFA has been compared vs. the original WFA.